Hepatocellular adenomas in the Turkish population: reclassification according to updated World Health Organization criteria - ÇELİKEL, ÇİĞDEM (WILEY, 2021)
Aims Hepatocellular adenoma (HCA) is an uncommon liver neoplasm, and studies of HCA subtypes have been primarily limited to France, the USA, and Japan. The aim of this study was to describe the clinicopathological features of HCA subtypes in Turkey. Methods and results The resection specimens of 59 cases diagnosed as 'hepatocellular adenoma' collected from 15 institutions were reviewed to confirm the diagnosis and to classify them according to the current World Health Organization 2019 classification. Immunostaining for glutamine synthetase, liver fatty acid-binding protein, C-reactive protein, beta-catenin and reticulin was performed. Of the 59 cases, 48 (81%) were diagnosed as HCA. We identified 24 (50%) hepatocyte nuclear factor 1 alpha (HNF1 alpha)-inactivated HCAs, five (10%) inflammatory HCAs, 15 (32%) beta-catenin-activated HCAs, three (6%) beta-catenin-activated inflammatory HCAs, and one (2%) unclassified HCA. HCA patients were predominantly female (female/male ratio of 5:1); they had a median age of 34 years and a median tumour diameter of 60 mm. In the beta-catenin-activated HCA group, nine cases (19%) showed cytoarchitectural atypia, and were also referred to as atypical hepatocellular neoplasms. In the beta-catenin-activated HCA group, three cases (6%) showed focal areas supportive of transition to HCA. The original diagnosis of HCA was changed to well-differentiated hepatocellular carcinoma in nine cases and to focal nodular hyperplasia in two cases. Conclusion In our series, the major HCA subtype was HNF1 alpha-inactivated HCA. We found a low incidence of inflammatory-type HCA. Our data also showed that beta-catenin-activated hepatocellular neoplasms, including cases with atypical histology, constituted a relatively high proportion of the cases. These findings are in contrast to those of most other studies of HCA subtypes.
Keywords: atypical hepatocellular neoplasm; hepatocellular adenoma; hepatocellular carcinoma